Iot Based Earthquake Warning System - Mrs. Mohana Priya, S. Sharon Anisha Angelin, S. Racshini, R. Shanmuga Priya (International Journal of Advanced Science and Technology, 2020)
IoT is a system to operate our daily basis thing by network. Earthquakes are caused by the shake in the surface of the earth. That shake may lead to waves, first the S waves starts to arise from the surface of the earth and then the P wave arises which is faster and terrible than the S waves. The waves even lead to road break. So, it is safer to find the earthquake during the S wave. In this paper, we proposed a system to find earthquake by IoT based system which identifies the earthquake during the S waves and then it alerts the people by displaying it as alert and the place where the earthquake has occurred. No human knowledge is required to operate this system so it is easy to handle the IoT based system, it operates automatically. So many lives can be saved by this system.